Ethnomedicine and Knowledge Transmission among Dayak Communities in Central Kalimantan: An Ethnographic Inquiry - Adawiyah, Rabiatul; Fatchurahman, M.; Pratomo , Guntur Satrio; Haris, Ferdiyani; Prajnashwari, I Gusti Ayu Raya; Wandianti, Sonia Lomei; Salsabina, Salsabina; Adhika Wiratama, Abid Naufal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Traditional medicinal knowledge is central to cultural identity and community well-being among the Dayak communities of Central Kalimantan yet its continuity is increasingly threatened by modernization and declining youth engagement. This study aims to examine how ethnomedicinal knowledge is transmitted practiced and sustained through therapeutic traditions eco spiritual values and intergenerational learning. Methods: A qualitative ethnographic approach was conducted in four regions of Central Kalimantan involving twelve purposively and snowball-selected participants including traditional leaders elders and women healers. This design was chosen to capture culturally embedded meanings that cannot be accessed through quantitative techniques. Data were collected through participant observation in depth interviews and documentation then transcribed verbatim and analyzed using thematic coding procedures. Results: Three major findings emerged. First the transmission of medicinal plant knowledge is weakening as younger generations increasingly rely on biomedical services. Second ritual practices such as offerings prayers and ecological ethics remain central in legitimizing healing and guiding responsible plant harvesting. Third the perceived effectiveness of key plants including kalakai pasak bumi and bajakah is reinforced through lived experiences of vitality and longevity although sustainability is challenged by shifting health preferences and environmental change. Conclusion: Dayak ethnomedicine reflects an integrated system combining therapeutic efficacy cultural identity and ecological stewardship. The findings highlight the importance of eco spiritual practices and intergenerational dynamics in sustaining traditional healing. Strengthening documentation pharmacological validation and youth-focused digital revitalization initiatives is essential for ensuring the resilience of Dayak ethnomedicinal knowledge.